Klotho supplementation attenuates blood pressure and albuminuria in murine model of IgA nephropathy. Issue 8 (August 2021) - Takenaka, Tsuneo; Hasan, Arif; Marumo, Takeshi; Kobori, Hiroyuki; Inoue, Tsutomu; Miyazaki, Takashi; Suzuki, Hiromichi; Nishiyama, Akira; Ishii, Naohito; Hayashi, Matsuhiko
Abstract : Background: Klotho interacts with various membrane proteins, such as transforming growth factor-β (TGFβ) and insulin-like growth factor (IGF) receptors. The renal expression of klotho is diminished in chronic kidney disease. Method: In this study, we assessed the effects of klotho supplementation on a murine model of IgA nephropathy. Twenty-four-week-old hyper serum IgA (HIGA) mice were subcutaneously injected daily with recombinant human klotho protein (20 μg/kg per day) or the vehicle. After 2 months, the mice were killed using an anesthesia overdose and their kidneys were harvested for analysis. Results: Supplementation of exogenous klotho protein reduced SBP, albuminuria, 8-epi-prostaglandin F2α excretion, glomerular filtration rate, renal angiotensin II concentration, and angiotensinogen expression in HIGA mice. Additionally, it enhanced renal expression of superoxide dismutase (SOD) and renal klotho itself. The findings using laser-manipulated microdissection demonstrated that klotho supplementation reduced the glomerular expression of TGFβ, fibronectin, and IGF, and increased the glomerular expression of connexin (Cx) 40. Conclusion: These results indicate that klotho supplementation reduces blood pressure by suppressing the renin–angiotensin system in HIGA mice. Klotho inhibits IGF signaling to preserve glomerular Cx40 levels, ameliorating albuminuria in HIGA mice. Klotho protein supplementation attenuates mesangial expansion by inhibiting TGFβ signaling in HIGA mice. Abstract : Supplemental Digital Content is available in the text